Imaging mass spectrometry of the visual system: Advancing the molecular understanding of retina degenerations. Issue 4 (28th January 2016) - Bowrey, Hannah E.; Anderson, David M.; Pallitto, Patrick; Gutierrez, Danielle B.; Fan, Jie; Crouch, Rosalie K.; Schey, Kevin L.; Ablonczy, Zsolt
Abstract : Visual sensation is fundamental for quality of life, and loss of vision to retinal degeneration is a debilitating condition. The eye is the only part of the central nervous system that can be noninvasively observed with optical imaging. In the clinics, various spectroscopic methods provide high spatial resolution images of the fundus and the developing degenerative lesions. However, the currently utilized tools are not specific enough to establish the molecular underpinnings of retinal diseases. In contrast, mass spectrometric imaging (MSI) is a powerful tool to identify molecularly specific disease indicators and classification markers. This technique is particularly well suited to the eye, where molecular information can be correlated with clinical data collected via noninvasive diagnostic imaging modalities. Recent studies during the last few recent years have uncovered a plethora of new spatially defined molecular information on several vision‐threatening diseases, including age‐related macular degeneration, Stargardt disease, glaucoma, cataract, as well as lipid disorders. Even though MS inside the eye cannot be performed noninvasively, by linking diagnostic and molecular information, these studies are the first step toward the development of smart ophthalmic diagnostic and surgical tools. Here, we provide an overview of current approaches applying MSI technology to ocular pathology.